Sarcoma de Ewing epidural lombar primário: Relato de caso - Kadri, Paulo Abdo Do Seixo [UNIFESP] (2002)
We report a case of a 15-years old female with an acute paraparesis secondary of an epidural mass and histopathological diagnosis was consistent with an Ewing's sarcoma without bone compromise. An exaustive literature review showed only 17 cases of primary lumbar epidural extraosseus Ewing's sarcoma.